Research on the evolutionary game of multi-agent collaborative supervision of enterprise green behavior driven by big data - Huo, Hong; Wang, Yue (Frontiers in Environmental Science, 2023)
Based on evolutionary game theory, this paper constructs a tripartite game model—involving the government, enterprises, and environmental protection social organizations—to explore an effective path for the collaborative supervision of corporate green behavior by multiple agents in the context of modern digital technology. The impacts of participating agent strategies are analyzed numerically, and the key factors affecting the ideal state are explored and simulated. The main conclusions and insights are as follows: (1) An increase in government information disclosure can effectively constrain enterprises’ behavior, by confronting them with the prospect of loss of reputation. However, if the enterprises’ loss of reputation is excessive, they will feel over-regulated, , which is not conducive their carrying out green innovation. Information disclosure does, however, have a role to play in transmitting environmental information to the public and environmental protection social organizations in a timely manner to reduce the information gap and promote the formation of multi-dimensional common governance. (2) By using big data, the government can not only save on government costs, but also more accurately identify and monitor in real time enterprises that are causing pollution and that are not using green technology. This can notably promote the evolution of all parties to an ideal state and improve the effectiveness of regulation. (3) When environmental social organizations provide enterprises with the necessary resource supports, this can significantly promote improvements in the enterprises’ level of enterprises' green technology innovation. (4) Increased willingness on the part of the public to supervise can enhance the interaction between the public and environmental social organizations, prompting those organizations to actively carry out environmental protection activities and increase their popularity among the public, which will have a positive effect on how the system involving government, enterprises, and environmental protection social organizations evolves.